Characterizing and understanding the formation of cysteine conjugates and other by-products in a random, lysine-linked antibody drug conjugate. Issue 1 (1st January 2021) - Qiu, Difei; Huang, Yande; Chennamsetty, Naresh; Miller, Scott A.; Hay, Michael
ABSTRACT: This study describes the characterization of conjugation sites for a random, lysine conjugated 2-iminothiolane (2-IT) based antibody-drug-conjugate synthesized from an IgG1 antibody and a duocarmycin analog-based payload-linker. Of the 80 putative lysine sites, 78 were found to be conjugated via tryptic peptide mapping and LC-HRMS. Surprisingly, seven cysteine-linked conjugated peptides were also detected resulting from the conjugation of cysteine residues derived from the four inter-chain disulfide bonds during the reaction. This unexpected finding could be attributed to the free thiols of the 2-IT thiolated antibody intermediates and/or the 4-mercaptobutanamide by-product resulting from the hydrolysis of 2-IT. These free thiols could cause the four inter-chain disulfide bonds of the antibody to scramble via intra- or inter-molecular attack. The presence of only pair of non-reactive (unconjugated) lysine residues, along with the four intact intra-chain disulfide bonds, is attributed to their poor accessibility, which is consistent with solvent accessibility modeling analysis. We also discovered a major by-product derived from the hydrolysis of the amidine moiety of the N -terminus conjugate. In contrast, the amidine moiety in lysine-linked conjugates appeared stable. Based on our results, we propose plausible formation mechanisms of cysteine-linked conjugates and the hydrolysis of the N -terminus conjugate, which provide scientific insights that are beneficial to process development and drug quality control.